2021
DOI: 10.3390/ijms23010035
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia Enhances Doxorubicin Therapeutic Efficacy against A375 and MNT-1 Melanoma Cells

Abstract: Melanoma is the deadliest form of skin cancer, and its incidence has alarmingly increased in the last few decades, creating a need for novel treatment approaches. Thus, we evaluated the combinatorial effect of doxorubicin (DOX) and hyperthermia on A375 and MNT-1 human melanoma cell lines. Cells were treated with DOX for 24, 48, and 72 h and their viabilities were assessed. The effect of DOX IC10 and IC20 (combined at 43 °C for 30, 60, and 120 min) on cell viability was further analyzed. Interference on cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 88 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Altogether, these results indicate that oxidative stress was increased in the melanoma microenvironment by the combined sequential therapy without triggering compensatory antioxidant protective mechanisms in tumor cells. The overall pro-oxidant state might be attributed to the reported cytotoxic effects of DOX which are induced by generation of reactive oxygen species in targeted cells ( Asensio-López et al, 2017 ; Salvador and Bastos, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these results indicate that oxidative stress was increased in the melanoma microenvironment by the combined sequential therapy without triggering compensatory antioxidant protective mechanisms in tumor cells. The overall pro-oxidant state might be attributed to the reported cytotoxic effects of DOX which are induced by generation of reactive oxygen species in targeted cells ( Asensio-López et al, 2017 ; Salvador and Bastos, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…DOX cytotoxic effects are induced by inner mitochondrial membrane localization and ROS production which enhances intracellular toxicity ( Montalvo et al, 2020 ). In melanoma, DOX is reported to induce cell cycle arrest, oxidative stress, and apoptosis if administered in combination with other factors that overcome intrinsic DOX resistance ( Licarete et al, 2020 ; Salvador and Bastos, 2021 ). Therefore, we next investigated the effects of the targeted sequential therapy consisting of IL-13-LCL-SIM and PEG-EV-DOX on oxidative stress parameters and apoptotic status in the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Mantso and colleagues [ 28 ] also exposed A375 cells to 43 °C for 2 h and to DTIC (5, 10, 30 μM) for 24–72 h. The results are similar to ours, showing that exposing cells to DTIC in combination with hyperthermia had a significantly potentiated effect on reducing cell viability at 48–72 h post-exposure, while at 24 h no significant changes were observed [ 28 ]. In our previous work with A375 and MNT-1 cells, we also observed that the potentiated effect of doxorubicin by hyperthermia was dependent on the drug concentration and heat period, demonstrating that not all combined drug and hyperthermia treatments are efficient [ 21 ]. Considering our results and with the aim of using a low DTIC concentration and small heating period with a significantly enhanced effect, an exposure time of 30 min to hyperthermia and 48 h to IC20 (5.5 μg/mL to A375 and 115 μg/mL to MNT-1) were selected to the following experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Combinatorial treatments have been showing promising results in melanoma treatment, from which can be highlighted hyperthermia and immunotherapy [ 63 ], radiotherapy and immunotherapy [ 64 ], and hyperthermia combined with chemotherapy [ 21 ]. Here, we demonstrated that combining hyperthermia with DTIC can be a promising alternative to apply in a primary or metastatic melanoma treatment, as shown by A375 and MNT-1 cells, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation